How to deal with coronavirus disease 2019: A comprehensive narrative review about oral involvement of the disease. Issue 1 (5th October 2020) - Capocasale, Giorgia; Nocini, Riccardo; Faccioni, Paolo; Donadello, Dario; Bertossi, Dario; Albanese, Massimo; Zotti, Francesca
Abstract: Objectives: The aim of this narrative review was to collect all findings from literature about oral signs and symptoms of COVID‐19, in order to draw a picture of oral involvement of this challenging viral infection, to help oral professionals in a better triage and early diagnosis. Material and methods: The search for international literature was made including articles written in English and reporting about oral manifestations in patients with a diagnosis of COVID‐19. The publication time was limited to 2019 and 2020, up to May 20, 2020. A narrative review was performed. Results: Twenty‐three articles were included in this review. Three different oral manifestations were found: taste alteration, oral blister and ulcers, and oral lesions associated with Kawasaki‐like diseases (erythema, bleeding of lips, "strawberry tongue"). The higher expression of Angiotensin‐converting enzyme 2 in the oral cavity and in endothelial cells might be responsible for oral manifestation and the major report of signs and symptoms in the occidental countries. Conclusions: Detecting oral signs and symptoms of COVID‐19 could be useful to perform a better preliminary triage in dental setting, and in recognizing possible early manifestations of the disease. However, considering the outbreak of COVID‐19 and the consequent difficulty of undergoing oral examinations, the oral manifestations might be misdiagnosed; then, we would encourage oral professionals to perform other studies about this topic.